Umbilical Cord Blood-Derived Exosomes From Very Preterm Infants With Bronchopulmonary Dysplasia Impaired Endothelial Angiogenesis: Roles of Exosomal MicroRNAs - Zhong, Xin-qi; Yan, Qin; Chen, Zhuang-gui; Jia, Chun-hong; Li, Xiu-hong; Liang, Zi-yan; Gu, Jian; Wei, Hui-ling; Lian, Chang-yu; Zheng, Jing; Cui, Qi-liang (Frontiers in Cell and Developmental Biology, 2021)
Premature infants have a high risk of bronchopulmonary dysplasia (BPD), which is characterized by abnormal development of alveoli and pulmonary vessels. Exosomes and exosomal miRNAs (EXO-miRNAs) from bronchoalveolar lavage fluid are involved in the development of BPD and might serve as predictive biomarkers for BPD. However, the roles of exosomes and EXO-miRNAs from umbilical cord blood of BPD infants in regulating angiogenesis are yet to be elucidated. In this study, we showed that umbilical cord blood-derived exosomes from BPD infants impaired angiogenesis in vitro. Next-generation sequencing of EXO-miRNAs from preterm infants without (NBPD group) or with BPD (BPD group) uncovered a total of 418 differentially expressed (DE) EXO-miRNAs. These DE EXO-miRNAs were primarily enriched in cellular function-associated pathways including the PI3K/Akt and angiogenesis-related signaling pathways. Among those EXO-miRNAs which are associated with PI3K/Akt and angiogenesis-related signaling pathways, BPD reduced the expression of hsa-miR-103a-3p and hsa-miR-185-5p exhibiting the most significant reduction (14.3% and 23.1% of NBPD group, respectively); BPD increased hsa-miR-200a-3p expression by 2.64 folds of the NBPD group. Furthermore, overexpression of hsa-miR-103a-3p and hsa-miR-185-5p in normal human umbilical vein endothelial cells (HUVECs) significantly enhanced endothelial cell proliferation, tube formation, and cell migration, whereas overexpressing hsa-miR-200a-3p inhibited these cellular responses. This study demonstrates that exosomes derived from umbilical cord blood of BPD infants impair angiogenesis, possibly via DE EXO-miRNAs, which might contribute to the development of BPD.